Register Video Editing in Capcut Application: Sociolinguistic Studies - Hanifah, Siti (Raudhah Publisher, 2024)
This study aims to describe the form and meaning of registers in video editing in the CapCut application. The source of this research data is videos on the YouTube channel that discuss editing tutorials in the CapCut application. This study uses a qualitative descriptive research method with a descriptive approach. The technique used in this study is to look and note. The type or form of register uses Halliday's theory. The results of the study found 2 lingual registers, 8 open registers and 9 limited registers. This research can increase the understanding of the science of registers and the use of language in today's digital environment.